Summary report of a digestibility trial with Atlantic salmon (Salmo Salar) in seawater as a model to predict raw material digestibility for European Catfish (Silurus glanis) ... - Koppe, Wolfgang; Meiske, Sven-Ole; Lamborelle, Georges; Sutter, David (Zenodo, 2022)
Confidential report ... : Funding: Garant ...